2006
DOI: 10.1128/jb.188.4.1518-1525.2006
|View full text |Cite
|
Sign up to set email alerts
|

A Mobile Quorum-Sensing System inSerratia marcescens

Abstract: Quorum-sensing systems that have been widely identified in bacteria play important roles in the regulation of bacterial multicellular behavior by which bacteria sense population density to control various biological functions, including virulence. One characteristic of the luxIR quorum-sensing genes is their diverse and discontinuous distribution among proteobacteria. Here we report that the spnIR quorum-sensing system identified in the enterobacterium Serratia marcescens strain SS-1 is carried in a transposon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…Almost all AHL producing strains were belonged to proteobacteria and to our knowledge, most of the LuxI/ R related QS genes have also been identified in this phylum. Therefore, the presence of QS regulation have already been confirmed by various studies in all isolates including Staphylococcus (Zhang et al, 2004), Serratia (Wei et al, 2006), Pseudomonas sp. (Juhas et al, 2005), Klebsiella (Balestrino et al, 2005), Psychrobacter (Jay et al, 2003) and Delftia sp.…”
Section: Screening Of Ahls Producing Bacteriamentioning
confidence: 62%
“…Almost all AHL producing strains were belonged to proteobacteria and to our knowledge, most of the LuxI/ R related QS genes have also been identified in this phylum. Therefore, the presence of QS regulation have already been confirmed by various studies in all isolates including Staphylococcus (Zhang et al, 2004), Serratia (Wei et al, 2006), Pseudomonas sp. (Juhas et al, 2005), Klebsiella (Balestrino et al, 2005), Psychrobacter (Jay et al, 2003) and Delftia sp.…”
Section: Screening Of Ahls Producing Bacteriamentioning
confidence: 62%
“…Using an approach described previously for Ti plasmid isolation (26), however, we failed to isolate the putative plasmid. One possible explanation for this failure is that this plasmid is too large to be isolated by routine methods, and the other possibility is that the QS2 system is carried not on a plasmid but in an integrative conjugative element, similar to the transmissible QS system in Serratia marcescens (46). It has been suggested that the multiple QS systems in most bacteria appear to have been acquired from separate sources (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…Lateral gene transfer may conceivably play an important role in driving the transfer of quorum-sensing units between different bacterial species (Boucher et al, 2003;Lerat and Moran, 2004). Interestingly, we have discovered that in S. marcescens SS-1, the spnIR quorum-sensing genes are located within a novel Tn3 family transposon termed TnTIR (Wei et al, 2006). The position of spnIR within the transposon is therefore likely to enhance opportunities for horizontal transfer of quorum-sensing genes and so increase the frequency of gene acquisition and evolution within microbial genomes.…”
Section: Horizontal Transfer Of Quorum-sensing Systems In Serratiamentioning
confidence: 95%